Women as Candidates in American Politics - Carroll, Susan (Indiana University Press, 1994)
In this second edition, Susan Carroll updates her pioneering study of women candidates and their campaigns in the aftermath of the "Year of the Woman." Although in many regards the political climate has become vastly more favorable for female candidates, opportunities are still limited by the political structure. Carroll examines a number of possible reforms and actual developments which may eventually mean larger numbers of women being elected to public office.